KESEJAHTERAAN PSIKOLOGIS DALAM MASA PANDEMI COVID-19 - Yunita Sumakul; Shanti Ruata (Institut Agama Kristen Negeri Manado, 2020)
Psychological well-being is a condition in which a person’s psychological aspects can function properly and positively. This study describes how the psychological well-being of parents who have dual roles in the Covid-19 pandemic period. This study used a descriptive qualitative approach. Participants in this study were working mothers and who have children in elementary schools. Data collected through observation, interviews, and documentation to participants and their families. The result showed that the Covid-19 pandemic disrupted the psychological well-being of participants. The psychological condition experienced are stress, fear, and anxiety related to the danger of Covid-19 transmission and the conditions of “stay at home´caused by the covid-19 pandemic.